Evaluation of Performance of Pinus caribaea Provenances in Sub-Himalayan Tract of West Bengal - Lahiri, A. K.; Choudhuri, P. K. Roy (Indian Forester, 1990)
The study reveals that the growth of Pinus cariboea was distinctly superior to other pines. The height growth of FRI-660 was better than FRI-659, 649, 662 and 562. The provenance FRI-660 proved the best performance.